O registro reflexivo na Educação Infantil - Santos, Lia Mara dos (2019)
This study aimed at analyzing the contributions of the reflective record to the professional development of preschool teachers from a private school located in the countryside of São Paulo. To do so, we reflected on how it can promote changes in teaching practices and on whether it is a valuable resignification strategy. Thus, we focused on the search for broaden pedagogical intentions and on the analysis of the relevance of an eighteen months record. Our theoretical framework used was essentially based on reflexive thinking by John Dewey (1979). In addition to Dewey, we also based this study on Sá-Chaves and Sadalla (2008), Lorieri (1997), Almeida (2001; 2012; 2015), Freire (1996; 2014) and Larrosa (2002; 2016). This is a qualitative research as it implies the documental analysis of teachers’ records. Through data analysis, it was possible to establish a few categories, namely: the relationships issue, children’s potentialities, the moments of enchantment with teaching, the feeling of competence and incompetence, the anguish surrounding the pedagogical practice, the personal and teaching overview, the relationship between theory and practice and, finally, the resignification and reconstruction of the teaching practice. The results for these categories showed that records are potentially self-formative and impact on teaching practices, in a process of permanent reconstruction of teachers’ experiences and their relationships with the school. Furthermore, results also revealed formative needs, such as changes in the teacher’s role conception, in the curriculum and the need to continue writing as a problematizing instrument at service of teacher reflexivity, fostering meaning to the teaching practice